-4/7=8-2f/3

Simple and best practice solution for -4/7=8-2f/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4/7=8-2f/3 equation:


-4/7=8-2f/3

We simplify the equation to the form, which is simple to understand
-4/7=8-2f/3

Simplifying:
-0.571428571429=8-2f/3

Simplifying:
-0.571428571429=8-0.666666666667f

We move all terms containing f to the left and all other terms to the right.
+ 0.666666666667f=+8 + 0.571428571429

We simplify left and right side of the equation.
+ 0.666666666667f=+8.57142857143

We divide both sides of the equation by 00.666666666667 to get f.
f=12.8571428571

See similar equations:

| 2(5x+9)=-36+14 | | 79=3(r+1)+2(7r+4) | | 3(2t-5)-(2t-2)=-54-(5t+4) | | 2x-(3+5x)=3(2x+3)+6 | | f(-1)=-(x^2+2x-3) | | 3x+16=9x+46 | | 2+4b=4+3b | | 3/2(3x+3)=3(1-2x)+12 | | 0.5t=3.5 | | 2a+10=-8 | | 5x-3y=88 | | x+72+31=180 | | 12x=(6)(8) | | 4w+3x=0 | | 2ax+ab=ab+b | | 36+1-12h=4h | | 1.285714286y-14=-5 | | 2x+8=2x-10 | | -27+20r=33 | | 0.9x+0.6x-6=-9 | | 36-12h=4h+1 | | 4(7-x)=12 | | -2x+8y=-58 | | 36-12h=4h | | 10z-9-3z+2= | | 36-12b=b | | 22.43=4g+3.71 | | 12x+28=84 | | 9x+3=4(2x-1)+7 | | 2(2x+2)=4(x+1) | | 36-12+(-5b)=1b-2 | | -5x-y=-33 |

Equations solver categories